Psychometric propierties of Spanish versión of Working Alliance Inventory-Short (WAI-S) - Corbella, Sergi; Botella, Luis; Gómez, Antonia María; Herrero, Olga; Pacheco, Meritxell (Anales de Psicología / Annals of Psychology, 2011)
This paper presents a study of the psychometric properties of the Spanish short version of the Working Alliance Inventory. Method: 229 subjects received psychotherapy treatment in a private centre. The mean ages were 29.2 years old (SD=8.84). All patients answered the spanish version of the Working Alliance Inventory when they finished the third session of the therapy. The factor analysis indicated that the first factor is based by the items from the Tasks and Bonds subscale, whereas the sec-ond factor is based by the items from the Tasks and Goals subscale. It is possible to differentiate between the therapeutic alliance subscales in the theory level, but data show that items from Goals, Tasks and Bond are close related. Reliability coefficient based on the internal consistency of the spanish version of the Working Alliance Inventory (short version) is good. Results suggest that therapeutic alliance may be a more unified construct than is usually thought of.